Understanding the barriers in the sustained use of household biodigesters: Insights from Nepal using system thinking approach - Navin Kumar Jha; Sunil Prasad Lohani (Energy Strategy Reviews, 2025)
Promoting household biodigester (HBD) as a sustainable alternative to traditional cooking fuels remains a priority in developing countries. However, despite various initiatives, the sustained use of HBD as a primary cooking fuel has not been fully achieved. To understand barriers of HBD adoption, the complex interplay between technical, socioeconomic, and institutional factors necessitates a more holistic analysis. This research develops a comprehensive framework to systematically explore these interconnections and applies it to a case study of Nepal's HBD system to identify root causes of abandonment of HBDs. Using a systems thinking approach and qualitative system dynamics modeling through a causal-loop diagram (CLD), the study effectively incorporates the field input and local stakeholders' perception in mapping during the analysis of the dynamic processes within the HBD system. The findings reveal that although initial interventions were successful, the declining usage of HBD is linked to systemic issues such as inadequate post-installation support, inconsistent biogas yields, insufficient maintenance, migration, cultural resistance, and shifting policy priorities. These challenges correspond to well-known system archetypes, including ''limits to growth,'' ''shifting the burden,'' ''fixes that fail,'' and ''tragedy of the commons.'' The research recommends targeted policy interventions, such as extending financial incentives to cover post installation repair & maintenance, shifting from capacity-based to performance-based subsidies, enhancing technical training, addressing cultural barriers, improving digestate management, and ensuring policy coherence. By adopting these strategies, policymakers can better support the long-term sustainability of HBDs.